The Moderating Effect of Attention-Deficit Hyperactivity Disorder Symptoms on the Relationship Between Procrastination and Internalizing Symptoms in the General Adult Population - Oguchi, Mana; Takahashi, Toru; Nitta, Yusuke; Kumano, Hiroaki (Frontiers in Psychology, 2021)
Background: The symptoms of attention-deficit hyperactivity disorder (ADHD) are known to exacerbate the effect of cognitive-behavioral impairments on emotional burden. Although adults with ADHD frequently experience procrastination and internalizing symptoms such as depression and anxiety, few studies have examined whether the association between procrastination and internalizing symptoms differs by ADHD symptoms. Objective: This study aimed to examine the moderating effect of ADHD symptoms on the association between procrastination and internalizing symptoms. Method: A cross-sectional survey was conducted among 470 adults (mean age = 26.57, standard deviation = 2.93) using self-reported questionnaires: Adult ADHD Self-Report Scale, General Procrastination Scales, Patient Health Questionnaire-9, and State-Trait Anxiety Inventory. Conclusion: Participants with more substantial ADHD symptoms experienced more procrastination and internalizing symptoms than those with the less substantial ADHD symptoms. Therefore, procrastination constitutes the treatment target for those suffering from ADHD and comorbid internalizing symptoms. Alternatively, there was no enhancing effect of ADHD symptoms on the association between procrastination and internalizing symptoms. It is necessary to examine more precise and valid hypotheses and underlying mechanisms of procrastination in high and low ADHD symptom groups.